Acoustic Estimation Of The Particle Size Distributions Of Sulphide Ores In A Laboratory Ball Mill (The Southern African Institute of Mining and Metallurgy, 2000)
The acoustic signals emitted from a laboratory-scale ball mill were used for the estimation of the comminution of two complex sulphide ores, viz. Merensky and UG2 ores from the Bushveld Igneous Complex in South Africa. The digital acoustic signals were transformed to power spectral densities that could be related to particle size distributions (-75 µm to 4000 µm) in the mill by use of continuum regression. This approach is more general than principal component regression methods or Kalman filtering used previously and resulted in significantly more accurate calibration in the case of the Merensky ore, where approximately 93.4% of the variance in the particle size distributions could be explained. With fewer data available, the variance in the particle size distributions in the UG2ore could be explained less accurately (82.4%), but still satisfactorily. In addition, smaller particle sizes (less than 300 µm) could be modelled more accurately in the case of the UG2 ore.